Synthesis of Materials Al(OH)3 Based on Sand in Batam Island as a Geopolymer for Brick Materials - Ulfa Nabilla; Dianita Wardani; Amnur Akhyan; Roni Novison (International ABEC, 2021)
Bauxite sand is beach sand on the island of Batam which contains a lot of kaolin, this is the result of the FTIR test that has been tested. Kaolin has a good composition of alumina (Al₂O₃) and silica (SiO₂) compounds to produce geopolymer materials for quality building materials. The geopolymer material synthesis process uses materials, namely Batam island bauxite sand, fly ash from burning sugarcane waste, and redmud and then mixed with wet materials such as NaOH and Sodium silica which are varied as much as 7% and 5%. After the geopolymer material, XRD testing was carried out to determine the angle 2 on the geopolymer and continued with the process of making bricks with a mixture of geopolymer and clay materials and then molding them with brick molds manually. The bricks were given curing or heating treatment for 24 hours with temperature variations of 80°C and 90°C then aging or left in the open for 14 days, then the bricks will be tested by testing hardness, compressive strength and impact testing at the Mechanical Engineering workshop Caltex Riau Polytechnic. The results of the tests that have been carried out are found that the compressive strength of the geopolymer brick composition 1 at 90°C is the brick that has the highest compressive strength value of 12.84 kg/cm². Impact testing is to see the toughness value of a material increases the impact value, the object is getting more, in this test geopolymer brick composition 1 + 90°C and geopolymer brick Composition 2 + 80°C are materials that are not or easily brittle with an impact price of 0.0063 J/mm² and 0.0071 J/mm². In the Brinell hardness test, the highest value was found by geopolymer bricks with a composition of 1 + 90°C, after three experiments the average HB value was 83.21. is the highest HB value of other composition geopolymer bricks and ordinary bricks.